Study and visualization of microplastic particle content in reservoirs of the city of Brest using GIS-technologies - Tolkach, Galina W.; Tokarchuk, Svetlana M. (Journal of the Belarusian State University. Ecology, 2020)
The article presents the experience of using modern GIS technologies to visualize data on the content of microplastic particles in the reservoirs of the city of Brest.The study of the content of microplastic particles in reservoirs was carried out based on the developed methodology, which included six steps. An inventory of reservoirs of the city of Brest was conducted, 25 representative reservoirs were selected for field research purposes. The result of the study is a series of interactive hydrographic maps of the Brest city territory. Maps reflect the main stages of the study on the content of microplastic particles in the water bodies of the city of Brest. These maps are freely available on the Internet, can be viewed by other users, on their basis, one can create other maps using ArcGIS Online account. The received data and interactive maps can be used in assessment of the current state and implementation of measures to reduce the degradation of water bodies in the city of Brest. The developed technique can be applied to conduct similar studies for other territories as well as for other types of objects (rivers, canals, etc.).
Keywords: Brest; reservoirs; microplastic; interactive hydrographic map; GIS-technology; cloud technologies